A Simultaneous Cartoon‐Texture Image Segmentation and Image Decomposition Method. Issue 5 (1st September 2020) - Li, Yafeng; Zhao, Qijun; Zhang, Wenbo; Fan, Pan; Zhang, Renrui; Sun, Jieqi; Sun, Jieqi; Li, Jing
Abstract : Image segmentation and image decomposition are fundamental problems in image processing. Image decomposition methods for separating images into cartoon and texture components can effectively serve different image processing tasks because different components can be respectively treated in more effective way. However, image decomposition methods are currently simply taken as an independent preprocessing step, and particularly in image segmentation different effects of cartoon and texture components have not been considered. This paper presents a novel simultaneous cartoon‐texture image segmentation and image decomposition method to boost the performance of both segmentation and decomposition. We design a fast alternating optimization algorithm to solve the proposed model. Experimental results demonstrate the outstanding performance of the proposed method on both image segmentation and image decomposition.